Program Bimbingan Belajar dalam Meningkatkan Pemahaman dan Minat Belajar Siswa di Pekon Tapak Siring Kecamatan Sukau Kabupaten Lampung Barat - Awandi, Hafizh; Alfatih, Nanda Karunia; Nugroho, Rizky Teguh; Athaya, Syifa; Umamit, Nurulla Beliyana; Nabila, Laini; Premana, Ketut Sudire (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2023)
Education is a very important aspect in every country to ensure the preservation of the nation's life. Students, as the successors of the nation who are at the forefront, must be able to carry out the tri dharma of higher education, namely in the form of education, research and community service. As a form of student service to the community, the University of Lampung Real Lecture Work (KKN) Period 1 of 2023 was held. In carrying out this KKN, the Tapak Siring 1 group held a work program entitled "Study Guidance to Increase Students' Understanding and Interest in Learning in Pekon Tapak Siring, Kec. Sukau, Kab. West Lampung. In this program, students provide a forum in the form of tutoring outside of school for the children of Tapak Siring Pekon. The implementation is carried out for twenty-six days which is carried out at night, namely at 19.00 until it is finished. Even though the learning interests and abilities of children in understanding learning material differ, the overall results obtained are that children in Tapak Siring Pekon are able to understand, deepen and add to their understanding of learning material according to their respective grade levels. This is evidenced by the results of the evaluation in the form of a try out (TO) carried out by students. The hope is that this program can run in a sustainable manner by financing upper class children as mentors for their younger siblings who are still in the lower class. Kata Kunci: Bimbingan Belajar, Minat Belajar, Pemahaman Siswa, Pendidikan.